Ekonomi Kreatif Berbasis Limbah Kayu pada PT Kasih Jaya Sejahtera Malang - Ana Sopanah; Nova Risdiyanto Ismail; Rahayu Puji Suci; Riza Bahtiar Sulistyan (Universitas Nurul Jadid, 2024)
The purpose of this activity is to improve the skills of participants, especially housewives, in processing wood waste into products with sales value, while empowering them economically and socially. The methods used include three main stages: planning, implementation, and evaluation. In the planning stage, training needs are identified, materials are prepared, and tools and materials are procured. Implementation is carried out through the delivery of theoretical materials and direct practice, where participants are trained to process wood waste into products such as plaques and wall decorations. Evaluation is carried out qualitatively through interviews and open questionnaires to understand the experiences and perceptions of participants. The results show that the majority of participants felt that this training was very useful, although there were suggestions to extend the duration of the practical sessions. Participants also showed good abilities in producing creative products that have the potential to provide additional income. The implications of this activity are an increase in skills and economic opportunities for participants, as well as a positive contribution to the environment through the utilization of wood waste. This training also shows that a practice-based approach is very effective in developing new skills in the creative economy sector.